VD_FINDINFO HC / 2011 / 618 vom 13. Oktober 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, PRESTATION DE PRÉVOYANCE | 125 CC, 4 al. 1 CPC, 451 ch. 2 CPC, 452 al. 2 CPC, 466 CPC, 405 al. 1 CPC (CH)